Perioperative enhanced recovery after surgery protocols with anterior mediastinal ectopic parathyroid tumor - Xiaodan Zhu; Yingxia Yu; Kanghui Huang (Medicine, 2026)
Rationale: To summarize the perioperative nursing experience in the successful treatment of anterior mediastinal ectopic parathyroid tumors. Patient concerns: A 50-year-old female, who had previously undergone treatment for a parathyroid adenoma for 7 years, was admitted to the hospital because of recurrent pancreatitis, kidney stones, hypercalcemia (2.98 mmol/L), elevated parathyroid hormone levels (299 pg/mL), and an abnormal parathyroid gland discovered in an external hospital examination 2 months prior. Diagnoses: Primary hyperparathyroidism secondary to an anterior mediastinal ectopic parathyroid tumor. Interventions: After the patient was admitted to the hospital, an multidisciplinary team discussion was immediately organized and a multidisciplinary collaborative team consisting of endocrinology, radiology, thoracic surgery, general surgery, and nursing departments was formed. The multidisciplinary team evaluated the patient’s treatment and ultimately decided to perform pre-diaphragmatic tumor resection under 99 mTcO 4 -MIBI localization and developed a perioperative rapid recovery plan for the patient. Outcomes: The patient achieved rapid recovery and was discharged 2 days after surgery. At discharge, serum parathyroid hormone decreased to 16 pg/mL, and serum calcium decreased to 2.68 mmol/L.A follow-up intervention was conducted half a year after discharge, and the patient remained in good recovery condition. Lessons: A multidisciplinary enhanced recovery after surgery protocol with a clinical decision support system monitoring enables safe ultra-early discharge, addresses the unique challenges of anterior mediastinal ectopic parathyroid tumor surgery, and provides a replicable framework for complex endocrine perioperative care.